2008
DOI: 10.4005/jjfs.91.111
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Browsing on Dwarf Bamboo (Sasa nipponica) by Sika Deer and the Structure of Ground Beetle (Coleoptera: Carabidae) Assemblage

Abstract: 111 119. An overabundance of Sika deer Cervus nippon at Mt. Ôdaigahara, in west-central Japan has necessitated the introduction of exclusion fences to protect forest decline from excessive feeding damage. However, the effect of these exclusion fences on the biodiversity of arthropods within the protected areas has not been investigated. In this study we examined the relationships between the volume of dwarf bamboo Sasa nipponica , the major forage for the deer, on associated with browsing by deer and the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…As many carabid beetles are flightless and prefer more stable habitats [42][43][44], they would provide a good reflection of differences in microenvironments. The results of our study and of a study conducted in western Japan [31] suggest that deer grazing indirectly decreases carabid beetles, in contrast to results obtained in boreal forests [25][26][27][28]. It is noteworthy that more carrion beetles, dung beetles, and camel crickets were collected outside the exclosure than inside (Table 4).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…As many carabid beetles are flightless and prefer more stable habitats [42][43][44], they would provide a good reflection of differences in microenvironments. The results of our study and of a study conducted in western Japan [31] suggest that deer grazing indirectly decreases carabid beetles, in contrast to results obtained in boreal forests [25][26][27][28]. It is noteworthy that more carrion beetles, dung beetles, and camel crickets were collected outside the exclosure than inside (Table 4).…”
Section: Discussioncontrasting
confidence: 55%
“…The habitat preferences of Japanese carabid beetles are not well known, but because forest vegetation predominates and the summer climate is humid in the Japanese archipelago, it is likely that most carabid beetles would prefer a habitat where litter is abundant and the microclimate is more humid and stable. A study on the indirect effects of sika deer on ground-dwelling insects in western Japan showed that a species of large carabid beetle, Carabus kumagai (23-36 mm in length), was more abundant in a habitat containing more Sasa nipponica, a dwarf bamboo [31]. As many carabid beetles are flightless and prefer more stable habitats [42][43][44], they would provide a good reflection of differences in microenvironments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda et al . () noted that Carabus ( Leptocarabus ) species do not prefer a habitat where the percentage of foliage cover is low. The result that Carabus species were abundantly collected in Japanese spruce suggests that Japanese spruce presents a favorable habitat for large species among the three plantations.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, ten plots were constructed for a research project to estimate the effects of deer grazing on plants, soil, and insects (e.g., Ito and Hino 2004;Furusawa et al 2005Furusawa et al , 2011Ueda et al 2008Ueda et al , 2009. Each deerexclusion plot was enclosed by a 2-m-high fence to keep deer out (plot size, 5 9 10 m).…”
Section: Site Descriptionmentioning
confidence: 99%